2014
DOI: 10.1057/9781137426475
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequality in the Public Sector in Pakistan

Abstract: To my mother for her selfless contribution toward the education of many a poor girl, and her vision that we must get involved in turning people's lives around and giving them hope for a better future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 191 publications
(496 reference statements)
0
5
0
Order By: Relevance
“…More than half of the caregivers were male which is in contrast with international studies that have repeatedly found that the majority of caregivers are female [22]. This can be explained by the patriarchal structure of Pakistani culture including its households [23]. The survey was done on patients accessing a relatively expensive private pay hospital in Karachi, which has a literacy rate of over 75% [24].…”
Section: Discussionmentioning
confidence: 96%
“…More than half of the caregivers were male which is in contrast with international studies that have repeatedly found that the majority of caregivers are female [22]. This can be explained by the patriarchal structure of Pakistani culture including its households [23]. The survey was done on patients accessing a relatively expensive private pay hospital in Karachi, which has a literacy rate of over 75% [24].…”
Section: Discussionmentioning
confidence: 96%
“…These are portrayed by the challenges of mobility of women in a traditionally male-run environment that largely discourages female travel without male family members (Butt et al 2010). This can produce an adverse institutional atmosphere for women to progress socially or professionally (Chauhan 2014).…”
Section: Ideas To Improve Access In Pakistani Rasmentioning
confidence: 99%
“…Hence, the WID theory has become very relevant as far as education and empowerment of women is concerned (Chauhan, 2014). A popular and instructive theory in respect of women empowerment and education is the "Women in Development (WID) theory.…”
Section: Women In Development (Wid) Theorymentioning
confidence: 99%